Kebijakan Diskriminasi Buruh di Indonesia: Studi Kasus Buruh Perempuan di PT AICE - Azzahra, Sheila Zhafira; Lestari, Try Putri; Angela, Deni; Komarudin, Ujang (Prodi Sosiologi FISIP Universitas Teuku Umar, 2024)
This study aims to identify the form of discrimination against female workers in PT AICE's policies in 2017, and to evaluate the implementation of human rights in employement practices. Using qualitative research methods by means of library research, namely research that collects information and data using various library materials such as documents, books, magazines, historical stories, and others. The results show that PT AICE has violated Labor Law No. 13 of 2003 with discriminatory policies against female workers, such as not providing nutritious food and shuttle transportation for female workers who work at night. These violations are considered a form of violence and exploitation against women workers. In addition, patriarchal culture still influences inequitable access and opportunities for women in the labor sector, which is reflected in the company's unwillingness to fulfill the rights of women workers, such as reproductive rights, health insurance during pregnancy, and rights for women workers who work at night. These findings show that there are still many human rights violations against women in the world of work.